VOICE OF ’REBELLION’ IN NOVELS OF HINDI WOMEN WRITERS OF NON-HINDI STATE PUNJAB - Mittal, Neena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article analyses the tendencies of female rebellion in novels of Hindi women writers of Punjab and presents the rebellious form of women by female novelists who are in search of freedom from the mentality and social dwarfism imposed by patriarchal society. This philosophy of female rebellion is a gift of the Renaissance period in Indian society and is a reaction against women’s oppression. Earlier this rebellion remained silent due to family ties but after independence, the increase in women’s consciousness and rights gave this rebellion an active form. The writer has also said that women novelists have expressed the pain of women and have worked to bring awareness in the society, due to which women have got constitutional and legal rights equal to men. In this article, the complexities of women’s rebellion and its development have been assessed, which has become a medium to bring important changes not only in literature but also in society.